Does trust matter? Analyzing the impact of trust on the perceived risk and acceptance of nuclear power energy - Ryu, Yeonjae; Kim, Sunhee; Kim, Seoyong (Sustainability (Switzerland), 2018)
Recently, trust has been in vogue in the social sciences. However, in risk studies, there have been few causal models of trust. This study proposes and tests a causal model of trust in which (1) source credibility influences trust and (2) two kinds of trust-i.e., trust in government and trust in regulation-affect the perceived risk and acceptance of nuclear energy. Based on survey data with a sample of 1014 local residents living near a nuclear power station, we tested a causal model using structural equation modeling. As for the results of the analysis: first, we confirmed the validity of the proposed causal model of trust. Second, on the causal path, credibility directly influenced trust in government and trust in regulation and indirectly affected the perceived risk and acceptance of nuclear power. Third, the two kinds of trust had (in)direct impacts on perceived risk and acceptance. Trust in regulation had more power to explain perceived risks and acceptance than trust in government. Trust is important, but the kind of trust is more important.
Keywords: Causal model of trust; Source credibility; Trust; Trust in government; Trust in regulation